2021
DOI: 10.1093/pm/pnab061
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Innervation of the Hip Joint and Referred Pain: A Systematic Review of the Literature

Abstract: Objectives The aim of this literature review was to establish consensus with respect to the anatomic features of the articular branches innervating the hip joint, and the distribution of sensory receptors within its capsule. Methods Five electronic databases were queried, between January 1945 and June 2019. Twenty-one original articles providing a detailed description of sensory receptors about the hip joint capsule (13) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 19 publications
0
42
0
1
Order By: Relevance
“…The Kim et al and Shin et al 1,2 studies also confirmed the geography of articular branches to specific (and partially overlapping) capsular areas (quadrants) 17 through labrocapsular tears‐‐‐consistent with hip articular anatomy and Hilton's law 6,7 . This application allows bidirectional predictions: If an IGC is observed, the quadrant in which the labral tear is located can be predicted.…”
Section: Journeying To Other Planets: Applying the Articular Theory T...mentioning
confidence: 65%
“…The Kim et al and Shin et al 1,2 studies also confirmed the geography of articular branches to specific (and partially overlapping) capsular areas (quadrants) 17 through labrocapsular tears‐‐‐consistent with hip articular anatomy and Hilton's law 6,7 . This application allows bidirectional predictions: If an IGC is observed, the quadrant in which the labral tear is located can be predicted.…”
Section: Journeying To Other Planets: Applying the Articular Theory T...mentioning
confidence: 65%
“…For the remaining 30% patients who responded suboptimally to anterior neurolysis, one of the postulations is the contribution and sensitization of the posterior hip capsule as supported by our recent case series on posterior hip pericapsular neurolysis [ 12 ]. Anatomically, this is explained by the presence of nociceptors in the superoposterior labrum, which is predominantly innervated by the nerve to the quadratus femoris with contributions from the superior gluteal and sciatic nerves [ 14 , 15 , 16 ]. The concept of silent nociceptor activation secondary to fracture hip can explain the augmented pain intensity over posterior hip capsule [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Painful structures could include the iliopsoas muscle which sits immediately anteriorly to the hip joint and has been found to be painful in almost half of people with DDH pre-PAO 7 and/ or the anterosuperior aspect of the hip capsule and labrum which have been found to have dense nociceptive innervation. 57 Future studies need to confirm whether these changes can be modified, and whether improvements in these impairments are related to improvements in pain and the progression to hip OA and total hip joint replacement.…”
Section: Discussionmentioning
confidence: 99%